2002
DOI: 10.1080/02699050210155285
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of caregiver burden following traumatic brain injury

Abstract: Rehabilitation professionals need to provide support that includes ongoing assessment of needs and provides a resource for steering caregivers to potential sources for meeting those needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
2
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 27 publications
9
70
2
6
Order By: Relevance
“…[27]], which, in turn, plays a significant role in the burden perceived by the caregivers [e.g. [28]], years of education was included in the model. In addition, because years of schooling negatively correlated with current urgency (table 2), both variables were allowed to correlate.…”
Section: Resultsmentioning
confidence: 99%
“…[27]], which, in turn, plays a significant role in the burden perceived by the caregivers [e.g. [28]], years of education was included in the model. In addition, because years of schooling negatively correlated with current urgency (table 2), both variables were allowed to correlate.…”
Section: Resultsmentioning
confidence: 99%
“…withdraw social support, over-protect). During this maladaptive period, research has shown families to experience increased stress [41], burden [42], depression and decreased overall family functioning [43]. These problems impair the family member's ability to offer social support [44].…”
Section: Social Support After a Brain Injurymentioning
confidence: 99%
“…1,15 Caregiver coping style affects the survivor's quality of life and functional outcome, as well as family caregiver perceived burden. 16,17 Caregivers who use avoidant-coping strategies experience higher levels of burden and decreased quality of life, 17 whereas caregivers who use passive coping styles have a negative impact on survivors' functional outcomes, particularly reengagement in social participation.…”
Section: Tbi Caregiver Burdenmentioning
confidence: 99%